The impact of the experience variable on the implementation of basketball privatization requirements in the Syrian Arab Republic (Journal of Hama University, 2026)
The research aims to identify the extent of the application of privatization requirements for the game of basketball in the Syrian Arab republic, and to identify the variable impact of years of experience in the extent of the application of privatization requirements, The researcher used the descriptive analytical method for its suitability to the nature of the study, the questionnaire was used as a research tool, the most prominent conclusions of the study were that the application of the privatization requirements for the game of basketball in the Syrian Arab republic came at the average level, there is also a need to work on developing all fields related to the requirements to suit the privatization process and the most prominent of which is the administrative field k and the administrative system and structure inforce Syrian basketball is also weakness and inefficiency, lack of freedom to invest sports venues and facilities for basketball and there are no statistically significant differences in the application of privatization requirement depending on the variable years of experience
Keywords: privatization, basketball, Syrian basketball federation